Business Process Outsourcing Performance Evaluation: A Lean-Agile Framework and Its Empirical Validation - Oluyinka, Oludapo Samson; Cheng, Jack Kie; Puteri Fadzline, Muhamad Tamyez; Ayodele, Freida Ozavize (ESB Business School, 2016)
How do we know that a Business Process Outsourcing (BPO) company is performing well or not? The validation method of the hybrid constructs presented in this paper is fueled by the investigation on the empirical framework of such question. Cost and quality which are seen as key factors of measurement have received favorable attention from researchers in manufacturing and production industries. However, the business process outsourcing service industry faces challenges with the recent change in the supply chain management orientation to the business as a service across networks of corporations. Therefore, this paper provides a validation of the performance measurement framework for BPO service organizations. To our knowledge, this is the first of its kind to extensively explore both lean and agile literature and then conceptualize the literature into a hybrid framework. We evaluated the current/existing framework that measures performance effectiveness and efficiency under lean and agile methodologies, excavated 8 constructs and then conducted a reliability and validity test for validation.